The Prevalence of Sarcopenia in the Elderly: How the Consumption of Protein Supplement Interacts in Individuals of a Fortaleza Institution - Mesquita da Cruz, Caroline; Holanda, Ivanira Maria Moreira; Noronha, Marco Antonio Pessoa; Mesquita da Cruz, Marcos Paulo; Alves da Silva, Raimunda Marcia Cristina; Barbosa da Silva, Helena Aquila; Magalhaes Rego, Juliana da Cunha; Canuto, Kildere Marques (European Scientific Journal, ESJ, 2018)
Introduction: Sarcopenia is a natural disturb that usually affects older people consisting in strength and muscle mass loss. Sedentary lifestyle and nutritional habits are some inducing factors. Supplementation may contribute to improvements on life quality in elders predisposed to sarcopenia. Objectives: verify the relevance of protein supplementation on life quality of elders predisposed to sarcopenia. Assess the individual’s evolution along the study. Methods: protein supplementation application during 45 days on 13 elders, comparing them with 13 elders in control group without supplementation. Anthropometric measurements were performed before and after the 45 days period and evaluated for each participant, as well as their nutrition, individually. Results: We observed a improvement in some anthropometric measures, and a reduction in others, that might be explained by previous pathologies already diagnosed. Muscle mass changes were positive, according with specific reference measures. Some elders reported motor strength improvements, disposition and energy. Physical active participants showed more significant results and sedentary ones. Conclusion: positive outcomes were obtained from protein supplementation in older people, and more correlated studies are still necessary, considering the field’s relevancy to longevity and overall life quality.